PENINGKATAN HASIL BELAJAR IPA DENGAN METODE COLLABORATIVE LEARNING PADA SISWA KELAS III SDN 006 SAMARINDA ULU TAHUN PELAJARAN 2016/2017 - Gamar Al Haddar (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
This study aims to enhance students’ science achievement through implementing collaborative learning method toward students of class III in SDN 006 Samarinda Ulu. For that reason, the researcher conducted a classroom action research and aplied four stages; planning, implementation, observation and reflection.To collect the data, observation on teacher’s and students’ activities, evaluation test, and documentation were employed. This study applied three cycles, wherein each cycle consist of three meetings. Moreover, the researcher involved 24 students of class III at SDN 006 as the research subjects. Meanwhile, the students’ science achievement as the result of implementing collaborative learning method was the research object.At the pre-cycle, the students’ average score was 46.3 with percentage of achievement 25%, classified into poor category. Meanwhile, the percentage increased 25% in cycle 1, making up 50% with average score 57.5. Furthermore, at cycle 2, the students’ average score inclined 20.8%, making up 67 with 70.8% students successfully passed the passing grade. Their score was categorized in fair criteria. In addition, at cycle 3, the students experienced progress at 8.4% with average score 71.9 with 79.2% students successfully accomplished the passing grade and classified into good criteria. As the result, it can be concluded that the implementation of collaborative learning method has effectively increased students’ science achievement in class III at SDN 006 Samarinda Ulu.Key words : Collaborative learning method, science achievement.